The recoding of a society: The publishing platform of the Dutch Reformed Church and its capturing of social consciousness, 1916–1960 - Pienaar, Jacques (Stellenbosch Theological Journal, 2024)
The undercarriage of Afrikaner nationalist mobilisation was assembled by a small group of language engineers during the opening decades of the twentieth century. Particularly influential within this broad literary project were the Afrikaans clerics who clustered around the Zuid-Afrikaanse Bijbel Vereniging (ZABV, later N.G. Kerk Uitgewers van Suid-Afrika), the official publishing wing of the Dutch Reformed Church (DRC). Propped up by this platform, DRC writers contributed to the linguistic shape of Afrikaans and crucially steered the affixed matter of nation building along a defined religious route in the image of a Christian-National Afrikanerdom. By the start of 1940 a sociological function within the operation of the ZABV lent itself to the nationalist agenda of capturing the consciousness of Afrikaner society. This notably contributed to the creation of an indoctrinated and self-concealed Afrikaner bloc based on the perpetuated myth of an unquestioned and divinely affirmed national uniqueness.